Variation of weak cation-exchange polymer layers grafted on hydrophobic microfiltration membrane for protein separation - Mohd. Yusof, A. H. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
Preparation of material for protein separation can be done with controlled surface funcitionalizations on membranes. Photo-initiated surface-selective graft copolymerization was performed using entrapping method. Weak cation-exchange polymer brush structures were obtained using acrylic acid (AA) grafted on hydrophobic microfiltration membrane pore surfaces. Copolymerization of AA with "diluent" monomer acrylamide (AAm) and "cross-linker" monomer methylene bisacrylamide (MBAA) were done for variations of the grafted layer. Graft copolymer composition analysis had been performed using gravimetry. Performance characterizations had been done by measurements of membrane permeability at low and high pH and by reversible binding of a lysozyme. Result of this study shows that the membrane permeability sensitivity to changes in pH depending on type of modification, high with diluent and low with cross-linker. In addition to that, chemical cross-linking within grafted layers leads to a significant improvement because the dynamic protein binding capacity can be increased,